Multiwavelength observations of nova SMCN 2016-10a - one of the brightest novae ever observed - Aydi, E. (2018)
We report on multiwavelength observations of nova Small Magellanic Cloud Nova 2016-10a. The present observational set is one of the most comprehensive for any nova in the Small Magellanic Cloud, including low-, medium-, and high-resolution optical spectroscopy and spectropolarimetry from Southern African Large Telescope, Folded Low-Order Yte-Pupil Double-Dispersed Spectrograph, and Southern Astrophysical Research; long-term Optical Gravitational Lensing Experiment V- and I-bands photometry dating back to 6 yr before eruption; Small and Moderate Aperture Research Telescope System optical and near-IR photometry from ˜11 d until over 280 d post-eruption; Swift satellite X-ray and ultraviolet observations from ˜6 d until 319 d post-eruption. The progenitor system contains a bright disc and a main sequence or a sub-giant secondary. The nova is very fast with t2 ≃ 4.0 ± 1.0 d and t3 ≃ 7.8 ± 2.0 d in the V band. If the nova is in the SMC, at a distance of ˜61 ± 10 kpc, we derive MV, max ≃ -10.5 ± 0.5, making it the brightest nova ever discovered in the SMC and one of the brightest on record. At day 5 post-eruption the spectral lines show a He/N spectroscopic class and an Full Width at Half Maximum of ˜3500 km s-1, indicating moderately high ejection velocities. The nova entered the nebular phase ˜20 d post-eruption, predicting the imminent super-soft source turn-on in the X-rays, which started ˜28 d post-eruption. The super-soft source properties indicate a white dwarf mass between 1.2 and 1.3 M in good agreement with the optical conclusions.